Cardiac resynchronisation therapy in paediatric and congenital heart disease: differential effects in various anatomical and functional substrates. Issue 14 (22nd March 2009) - Janoušek, J; Gebauer, R A; Abdul-Khaliq, H; Turner, M; Kornyei, L; Grollmuß, O; Rosenthal, E; Villain, E; Früh, A; Paul, T; Blom, N A; Happonen, J-M; et al.
Abstract : Background: Cardiac resynchronisation therapy (CRT) is increasingly used in children in a variety of anatomical and pathophysiological conditions, but published data are scarce. Objective: To record current practice and results of CRT in paediatric and congenital heart disease. Design: Retrospective multicentre European survey. Setting: Paediatric cardiology and cardiac surgery centres. Patients: One hundred and nine patients aged 0.24–73.8 (median 16.9) years with structural congenital heart disease (n = 87), congenital atrioventricular block (n = 12) and dilated cardiomyopathy (n = 10) with systemic left (n = 69), right (n = 36) or single (n = 4) ventricular dysfunction and ventricular dyssynchrony during sinus rhythm (n = 25) or associated with pacing (n = 84). Interventions: CRT for a median period of 7.5 months (concurrent cardiac surgery in 16/109). Main outcome measures: Functional improvement and echocardiographic change in systemic ventricular function. Results: The z score of the systemic ventricular end-diastolic dimension decreased by median 1.1 (p<0.001). Ejection fraction (EF) or fractional area of change increased by a mean (SD) of 11.5 (14.3)% (p<0.001) and New York Heart Association (NYHA) class improved by median 1.0 grade (p<0.001). Non-response to CRT (18.5%) was multivariably predicted by the presence of primary dilated cardiomyopathy (p = 0.002) and poor NYHA class (p = 0.003). Presence of a systemic left ventricle was the strongest multivariable predictor of improvement in EF/fractional area of change (p<0.001). Results were independent of the number of patients treated in each contributing centre. Conclusion: Heart failure associated with ventricular pacing is the largest indication for CRT in paediatric and congenital heart disease. CRT efficacy varies widely with the underlying anatomical and pathophysiological substrate.